2013
DOI: 10.1007/s12975-013-0271-4
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Proteins in the Brain: Role of Hsp70, Hsp 27, and HO-1 (Hsp32) and Their Therapeutic Potential

Abstract: Heat shock proteins are induced by heat shock via HSF proteins binding to heat shock elements in their promoters. Hsp70 is massively induced in response to misfolded proteins following cerebral ischemia in all cell types, but is induced mainly in neurons in the ischemic penumbra. Over expression of Hsp70 via transgenes and viruses or systemic administration of Hsp70 fusion proteins that allow it to cross the blood brain barrier protect brain against ischemia in most reported studies. Hsp27 can exist as unphosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
102
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(107 citation statements)
references
References 39 publications
(83 reference statements)
2
102
1
2
Order By: Relevance
“…The inhibition of Hsp90 activity has been shown to induce increased expression of Hsp70 and Hsp90 via HSF-1 activation and is related to cell protection during stress (Sharp et al, 2013;Paul and Mahanta, 2014;Leung et al, 2015). Accordingly, we observed the induction of Hsp90 expression in LPSstimulated macrophages pretreated with gedunin, 17-AAG, and dexamethasone (which also modulates HSF-1 activity; Knowlton and Sun, 2001) (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 58%
“…The inhibition of Hsp90 activity has been shown to induce increased expression of Hsp70 and Hsp90 via HSF-1 activation and is related to cell protection during stress (Sharp et al, 2013;Paul and Mahanta, 2014;Leung et al, 2015). Accordingly, we observed the induction of Hsp90 expression in LPSstimulated macrophages pretreated with gedunin, 17-AAG, and dexamethasone (which also modulates HSF-1 activity; Knowlton and Sun, 2001) (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 58%
“…6,35) Thus, we further investigated the role of HSP70 in the protective effect of Zligustilide against OGD-Reoxy induced injury. The results Recent study demonstrated that overproduction of damaged proteins following focal cerebral ischemia increases protein ubiquitination, resulting in ubiquitinated proteins aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…4) It's reported that over-expression of HSP70 via transgenes and viruses or systemic administration of HSP70 fusion proteins that allow it to cross the blood brain barrier protects the brain against ischemia, 5,6) suggesting that increasing HSP70 level or activity may be a potential therapeutic target for pharmacological intervention of ischemic diseases.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Apaf-1 and cytochrome c to form the apoptosome complex; whereas GRP78 is abundantly expressed in the endoplasmic reticulum and is primarily responsible for binding onto newly synthesized proteins and maintains them in a state that allows them to be correctly folded and assembled in the endoplasmic reticulum, especially under pathological conditions where the accumulation of misfolded and unfolded proteins occur; known as endoplasmic reticulum stress that commonly develops during an ischemic stroke (Franklin et al, 2005;Giffard & Yenari, 2004;Gonzalez-Gronow et al, 2009;Luo et al, 2013;Ni et al, 2011;Niforou et al, 2014;Quinones et al, 2008;Sharp et al, 2013;Yenari et al, 2005). Both…”
Section: Protective Mechanisms Of Intermittent Fasting (If) In the Brainmentioning
confidence: 99%